Design and optimization of 2x2 corporate-series fed microstrip antenna array - George, Jobins; Lethakumari, B (International Journal of Engineering and Technology, 2018)
The limitation of microstrip patch antenna is relatively low gain and narrow bandwidth. By using the microstrip patch antenna array antenna performance can be improved. In this paper design and stimulation of a 4 element rectangular microstrip patch array is described and the performance of antenna array is optimized by varying patch element dimensions. Antenna array is designed to operated at the frequency of 10 GHz. The corporate-series feed network is implemented for feeding patch elements. The 2x2 antenna array is implemented on FR4 substrate with 1.588mm thickness and dielectric constant of 4.4.The stimulation and performance analyze of antenna is done using Ansoft High frequency structure simulator software. Finally, comparison of antenna arraycharacteristics before and after optimization is presented.